Analisis Yield Sedimen Saluran Sekunder Langgonaweeha Kecamatan Konawe - Haydir Haydir; Ardin Ardin (Universitas Batanghari Jambi, 2023)
The Wawotobi Irrigation Area on the Left Intake (Wawotobi Weir) has been equipped with a sediment catchment building but still has problems that occur routinely, namely sedimentation in irrigation canals, sedimentation results in changes in canal dimensions resulting in reduced canal capacity, decreased quality of water flowing in canals, and causes not optimal the function of the existing irrigation structures along the wawotobi irrigation area. The research study location is in the Langgonaweeha Secondary channel which is part of the D.I. Wawotobi, Konawe Regency, Southeast Sulawesi. The purpose of this study was to analyze the predictive value of the sediment yield that occurred in the Langgonaweeha Secondary Canal. The results of the analysis obtained the value of the average value (SY) of sediment yield of 0.0000000153 ton/ha/year. Whereas for the calculation of each Langgonaweeha Secondary canal section it is known that on the BBg3-Blg1 section it is obtained at 0.000012313 tons/ha/year and on the BLg1-BLg2 section it is obtained at 0.000017755 tons/ha/year, while on the BLg2-BLg3 section it is obtained at 0 .0000161075 ton/ha/year, then the prediction (SY) of sediment yield in the Langgonaweeha Secondary canal is 0.00000513060 ton/ha/year while the yield value of sediment in the Langgonaweeha Secondary canal is 0.001872673 per year. By recapitulating the average total volume of sediment, it is necessary to transport or dredge sediments so that long-lasting deposition does not occur which causes sagging and dimensional changes in the Langgonaweeha Secondary Canal.